Densidade da Madeira: Variável Fundamental na Determinação de Uso e Estimativa de Estoque de Biomassa Florestal - Novais, Thais de Nazaré Oliveira (Instituto Nacional de Pesquisas da Amazônia - INPA, 2022)
In the context of climate change, basic wood density is essential for quantifying forest biomass and for reducing uncertainties in biomass estimates for tropical forests. In addition, it contributes to the indication of potential commercial uses, mainly in the civil construction sector. However, there are few studies that describe density variations along the tree for tropical species. The present study intends to evaluate the vertical variability of wood density along the bole, fit equations and classify the uses of commercial species from the Amazon region. In total, 224 trees in 20 species were sampled, and these were categorized by type of wood as a function of density, resulting in: light-wood (≤ 0.40 g cm-3), medium-wood (0.41 – 0 .60 g cm-3) and heavy-wood (≥ 0.61 g cm-3) species. The variability of basic density of the wood along the bole varies by type of wood. In light-wood tree trunks, density increases with height, while it decreases in medium- and heavy-wood species. Thus, if only the basic density of the wood obtained at the bottom of the bole is considered, this will result in an underestimation of 2.89% for the density of the bole for light-wood species, and overestimations of 4.12% and 2.46%, respectively, for the medium and heavy wood species. These systematic biases will lead to significant errors if incorporated into large-scale forest biomass estimates. Through the above percentages and the equations developed to estimate the stem density, it is possible to correct for the vertical variation. Finally, it was found that wood density influences the use of the wood and its durability. Light-wood species and the majority of medium-wood species, due to their lower densities, are used for temporary products, which, after their use and discard, generate large amounts of residues that can contribute to the emission of greenhouse gases. In contrast, heavy-wood species, probably due to their high density, greater strength and natural durability, have products with a longer shelf life, keeping the carbon stored for longer periods of time.
Keywords: Densidade da Madeira